Criteria for selection of students for the elective course in the specialization «sports orienting» - Zagorodnikovа D.M. ,; Kapilevich L.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determination of criteria for the initial selection of students for an elective course in the specialization «Orienteering». Methods and structure of the study. The experiment was attended by NI TSU students aged from 18 to 21 years, 36 females and 25 males, specializing in «General Physical Training». Testing of cognitive abilities, physical fitness, as well as completion of a distance in the «cross-choice» discipline was carried out. Results and conclusions. The factors that determine the criteria for the initial selection of students to specialize in orienteering at the university have been identified. For men, this is the level of development of spatial thinking and working memory, the level of development of spatial thinking and short-term memory, the relationship between the development of short-term memory and the distribution and volume of attention and the performance of physical activity in an aerobic mode, endurance when performing specific work. For women, the determining factors were the level of development of spatial thinking and short-term memory, endurance when performing specific work, and the level of development of operational thinking. We recommend using the obtained data when selecting students for orienteering sports sections.